FISCAL COMPETITION AND DIRECT FOREIGN INVESTMENTS: ROMANIA VERSUS POLAND - Lazar Paula; Vuta Mariana; Vuta Mihai (Annals of the University of Oradea: Economic Science, 2012)
The European Economic Community treaty defines indirect taxation common rules taking into consideration their impact upon free merchandise’s circulation and upon international commercial exchanges. Once the Roma treaty has been signed (1957) the established scope was creating a common market. But, how is it possible to create a common market without any monetary and fiscal instruments? Thus, these instruments have had to be created in order to achieve such an objective. If from the monetary point of view introducing euro as a common currency was a big step ahead, from the fiscal point of view things haven’t evolved in such an easy manner. Fiscal objectives are achieved only if the national market is running normally and correctly. Indirect taxation is harmonized base upon article 113 from the European Union Treaty, while regarding direct taxation legal recommendations and regulations approval we can’t talk about harmonization but about fiscal competition. We are stating this because there are 27 states in the European Union and each one is sustaining its own direct taxation system. Furthermore, the taxation system (fiscal system) is influencing member states economical performances through economies, investments and human capital formation by affecting the revenue’s distribution, research and development expenses level and type and by fiscal competition – an effect more and more profound. In this context we aim at analyzing the way fiscal competition had had a positive impact upon attracting foreign direct investments in Romania and Poland. We also aim at underlining positive and negative points for fiscal competition taking into consideration that not only a decrease in micro or macro-economic fiscal burden will have a positive impact upon investments in-flows and there are other factors to be taken into consideration, like: infrastructure, labor expenses, research and development expenses, internet access, etc. The research is mainly based upon a synthesis of the reached area in the special literature. The study continues a fundamental research using deductive and inductive research mechanism in order to delimit the used concepts.